THEORETICAL ASPECTS AND METHODS OF INCREASING REGIONAL INVESTMENT ATTRACTIVENESS (E Global Congress, 2023)
The analysis of the socio-economic changes taking place in our country shows that the modernization of the economy and the role of active investment policy are very important in the achievements and successes. Accordingly, it is important to create an effective system for managing the socio-economic development of the regions of the republic, to study the theoretical and methodological basis for assessing the attractiveness and potential of their investment climate. In this regard, the Action Strategy for the five priority areas of development of the Republic of Uzbekistan for 2017-2021 was approved by Presidential Decree on February 7, 2017. According to him, the third priority is the further development and liberalization of the economy, which aims to actively attract foreign investment in sectors and regions of the economy by improving the investment climate [1].